LEAM vs. BEAM vs. CLV Conditioning Regimen for Autologous Stem Cell Transplantation in Malignant Lymphomas. Retrospective Comparison of Toxicity and Efficacy on 222 Patients in the First 100 Days After Transplant, On Behalf of the Romanian Society for Bone Marrow Transplantation - Colita, Andrei; Colita, Anca; Bumbea, Horia; Croitoru, Adina; Orban, Carmen; Lipan, Lavinia Eugenia; Craciun, Oana-Gabriela; Soare, Dan; Ghimici, Cecilia; Manolache, Raluca; Gelatu, Ionel; Vladareanu, Ana-Maria; et al. (Frontiers in Oncology, 2019)
High-dose chemotherapy (HDT) followed by autologous hematopoietic stem cell transplantation (ASCT) is widely used in patients with malignant lymphomas. Currently, only a few comparative studies, most of them retrospective, between different conditioning protocols regarding efficacy and toxicity have been published. Thus, in the current manuscript, we report the experience of 2 transplant centers in ASCT in R/R lymphomas with three types of conditioning: BEAM, CLV and LEAM. All patients developed grade IV neutropenia, anemia with/without transfusion necessity. Severe thrombocytopenia with transfusion requirements is reported in most cases. Median time to platelet engraftment and neutrophil engraftment was 13 days (range) and 10 days (range), respectively. Gastrointestinal toxicity was the most common nonhematologic toxicity after all three conditioning regimens. Oral mucositis in various grades from I to IV was diagnosed in most cases. Other side effects include vomiting, diarrhea, colitis and skin rash but with low severity grades. For the LEAM arm, one patient died after transplant, before engrafting, one patient didn’t achieve platelet engraftment in day 100, one patient developed grade 3 upper gastrointestinal bleeding, one patient died (grade 5 toxicity) with acute renal failure, one patient developed hypoxic events up to grade 4 acute respiratory failure and one patient developed grade 3 itchy skin rash. For the CLV arm, one patient died after transplant, before engrafting, one patient developed grade 3 colitis, one patient with grade 3 hepatic cytolysis, one patient with cardiac toxicity followed by death (grade 5) caused by an acute myocardial infarction with ST elevation and one patient with pulmonary toxicity clinically manifested with grade 3 pleurisy. For the BEAM arm, one patient developed grade 3 cardiac toxicity with sinus bradycardia and afterwards grade 4 with acute pulmonary edema, three patients presented a grade 3 pruritic skin rash and two patients developed grade 3 seizures. In the present study we presented the differences that were observed between BEAM, LEAM and CLV conditioning regimens offering clinical arguments for an SCT practitioner choice in the ideal situation, but also of choice for alternative regimens in the case that one regimen cannot be used.